Związki uczuciowe adolescentów w perspektywie rozwojowej – przegląd wyników badań - Kacprzak, Kamila (Wydawnictwo Naukowe UAM, 2015)
Young people engage into their first romantic relationships, which evolve and change in terms of both content and function. The aim of this article is to present the role and importance of adolescents’ romantic relationship in their further development and to describe these relations based on a review of research results found in English-language scientific articles. The structure of presentation follows the categories proposed by W.A. Collins: involvement, partner selection, contents, quality, cognitive and emotional processes. Analysis shows that engaging in a romantic relationship during the adolescence period may differentiate the execution of developmental tasks expected during the adolescence period and also the effects of relationships in early adulthood. The research results also show that adolescents’ romantic relationships are changeable and dynamic. The picture of these relations differs and depends on whether they were established during early or late adolescence. These properties are reflected in each of the analyzed categories.
Adolescents’ Romantic Relationships in the Developmental Perspective – Research Review
Keywords: adolescents; romantic relationship; developmental tasks